Pregnancy Married in the Perspective of Islamic Law and Five Mazhab - Nasruddin S.; Sulaemang L (Al-'Adl, 2021)
This research discusses the issue of pregnancy marriage from the perspective of Islamic Law and Five Mazhab. Marriage in Islam refers to a physical and mental bond, which is sacred and contains the value of worship. However, adultery often occurs leading to the illegal pregnancy causing the married by accident. As a result, to cover up the disgrace and survive, these pregnant women need to immediately marry either the man who impregnated her or someone else. Accordingly, whether the pregnancy married is possible according to the perspective of Islamic law and five mazhab, as well as the birth status of the child. The Islamic Law provides legality regarding the marriage of a pregnant woman on the condition that she is married to a man who impregnated her, in contrast, the mazhab perspective indicates the difference, some allow the marriage, some prohibit the action. Among those who allow it is the Hanafi Mazhab, allowing men who impregnate them, Shafi'i allows without any conditions and Ja'fari allows them to repent first. Meanwhile, those who do not allow are the Maliki and Hanbali Mazhab except with two conditions, namely willingness to repent and waiting for the `` iddah or waiting period. Regarding the child's family status, Article 100 of Islamic Law, states the child's family relationship status with the mother and the mother's family. Meanwhile, the scholars have different opinions, but the majority agree that children due to adultery are given services to their mothers.